Peningkatan Keterampilan Teknik Dasar Passing dengan Metode Drill pada Ekstrakurikuler Futsal di SMA Islam Kota Malang - Muhammad Farhan; Agus Tomi; Arief darmawan (Universitas Palangka Raya, 2023)
This research was conducted because the role of the coach still does not have a good and regular training program, so the purpose of this research is to improve basic passing technique skills for futsal extracurricular participants at the Islamic High School in Malang City by using the drill method. This research method uses Sports Action Research. This research is the same as Classroom Action Research which uses the stages of planning, implementing, observing, and reflecting. This study uses 2 cycles with 4 meetings in each cycle. The subjects of this study were 20 male participants in the futsal extracurricular activities at SMA Islam Malang City. From the results of the study showed an increase in basic passing technique skills in cycle 1 and cycle 2. In the initial observation it showed that the overall completeness of the participants was 49.28%, then it increased at the end of cycle 1 by 64,28% and increased again in cycle 2 of the final meeting by 88, 39%. With this, increased results were obtained from basic passing technical skills using the drill method for futsal extracurricular participants at Malang City Islamic High School. It can be concluded that the application of the drill method can improve basic passing technique skills for futsal extracurricular participants at Islamic High School in Malang City.